2020
DOI: 10.1097/olq.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure Prophylaxis Awareness and Use Among Cisgender Men Who Have Sex With Men and Use Methamphetamine in 3 Western US Cities

Abstract: Background In the United States, cisgender men who have sex with men (MSM) who use methamphetamine are at substantial risk for HIV and can benefit from pre-exposure prophylaxis (PrEP). Methods We used data from the National HIV Behavioral Surveillance 2017 survey from Seattle, WA; Portland, OR; and Denver, CO, to estimate PrEP awareness and use in the past 12 months among MSM who use methamphetamine. We then compared these estimates with participants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In our cohort, methamphetamine consumption was almost double that in other groups [ 22 , 25 ]. A more comprehensive and multidisciplinary approach to chemsex could avoid considerable individual and public health issues beyond HIV transmission [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, methamphetamine consumption was almost double that in other groups [ 22 , 25 ]. A more comprehensive and multidisciplinary approach to chemsex could avoid considerable individual and public health issues beyond HIV transmission [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a NYC survey, 41% of SMM had heard of PrEP, but only 3.4% of the sample had ever taken it [ 5 ]; in general, PrEP uptake rates are lower among young SMM than older SMM [ 20 ]. Among SMM, researchers found that PrEP awareness was significantly lower for methamphetamine users when compared with those who do not use methamphetamines (89% and 95%, respectively, p = 0.01), but there was no significant difference in actual PrEP use between the two groups [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States alone, prevalence of meth use among PLWHA was over 9% during 2015-2016 [86]. As per the National HIV Behavioral Surveillance (NHBS) 2017 survey from Seattle, WA; Portland, OR; and Denver, CO which involved 1,602 meth users, particularly men who have sex with men (MSM), and at substantial risk of HIV, reported that meth use most likely was the cause for low oral-preexposure prophylaxis (PrEP) awareness among the risk group [87]. Similar observations were noticed in a longitudinal study of the Swiss HIV Cohort performed during 2007-2017 where use of psychostimulants, including meth, was significantly associated with unsafe sex with frequent partners, and higher prevalence of mood disorders, sexually transmitted infections, and viral infections other than HIV [88].…”
Section: Incidence Of Methamphetamine Use Among Plwhamentioning
confidence: 99%